Assessing of tolerance to metallic and saline stresses in the halophyte Suaeda fruticosa: The indicator role of antioxidative enzymes - Bankaji, Insaf (2019)
Many areas are simultaneously affected by high concentrations of salts and trace metal elements (TME), the latter constituting a serious threat to human health. In the present study, we determined the combined effect of high salinity and toxic levels of trace elements on physiological behavior of the halophytic species Suaeda fruticosa. Plants were cultivated for three months with an irrigation solution supplemented separately with different concentrations of Pb2+ and Zn2+ (0, 200, 400 and 600 microM) with and without 200 mM NaCl. Growth, total chlorophyll, water status and ion nutrition were quantified and antioxidant enzyme activities [ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and catalase (CAT)] were studied. Our results revealed that S. fruticosa has a strong ability to tolerate lead and zinc. This halophyte accumulated higher concentrations of TME in their roots. Growth parameters of S. fruticosa were not significantly affected by TME. An enhancement of Ca2+ concentration accompanied by a decrease of Mg2+ content was observed under Pb2+ or Zn2+ treatments whereas K+ content was not affected by TME. Of the antioxidant enzymes, the activity of CAT and APX was increased by metal stress. However, the activity of GPX was diminished by increasing TME concentrations. It was concluded that NaCl 200 mM had a positive impact on the response of S. fruticosa to Zn2+ toxicity, acting through a decrease in Zn absorption.